HUBUNGAN PENGETAHUAN, SIKAP, DAN TINDAKAN IBU RUMAH TANGGA TENTANG PRAKTIK PENCEGAHAN DEMAM BERDARAH DENGUE DENGAN RUMAH BEBAS JENTIK DI RW 05 KELURAHAN TANAH PATAH KOTA BENGKULU TAHUN 2012 - Nofryadi, Robed (JURNAL MEDIA KESEHATAN, 2012)
Highest dengue cases in 2010 in the city of Bengkulu occurred in Nusa Indah health center with a higher IR 166 per 100.000 and 2,94% CFR. The housewife has a very important role in monitoring the presence of Aedes aegypti mosquito larvae in the home. The knowledge, attitude and positive action on the prevention of dengue by housewives, is expected to improve the status of the free larva. Formulation of research problem whether there is a relationship of knowledge, attitudes and actions the housewife on dengue prevention practices with free housing larva?. The purpose of research to know the relationship of knowledge, attitudes and actions the housewife on dengue prevention practices with free home larva. This type of research is a cross sectional analytic. Population 175 homes. Samples 122 homes. Sampling by proportional stratified sampling. Analysis conducted univariate and bivariate analyzes, usinf Chi Square test (χ2). The results of univariate analysis that, as much as 62,30% knowledgeable good. 51,64% to be good housewives. 65,57% housewives to act less more free housing portion 72,13% larvae in the high category. There is a correlation between knowledge, attitudes and action the housewife on dengue prevention practices with free houses flick in RW 05 Tanah Patah Bengkulu in 2012 expected that the need for cross-sectional collaboration across programs that dengue preventioan efforts can be implemented with a well directed and programmed.